Determinants of Cost Inefficiency and Farmer Performance in Broiler Contract Farming - J. M. M. AJi; M. Rondhi; A. Suwandari; T. D. Hapsari; J. Januar; R. Yanuarti; Rokhani (Faculty of Animal Science, Bogor Agricultural University, 2023)
The broiler industry plays an important role in meeting the growing demand for animal protein. Ensuring favorable farming conditions are needed to maintain the meat supply, and theoretically, this can be improved through the implementation of Contract Farming (CF). CF grants farmers the privilege to predict quantities, prices, and reduce production risks. However, one of the key challenges in establishing CF is the cost efficiency and performance of farmers. This study aims to develop a cost function for farmers, identify factors contributing to inefficiency, and evaluate farmer performance. The purposive sampling method is employed to select broiler farmers participating in contract farming as the sample for this study. Primary data were collected through surveys. Stochastic frontier cost analysis is utilized to derive a broiler cost function while examining the causes of farm inefficiency and their relationship with farmers’ performance variables. The results indicate that the broiler cost function is significantly influenced by labor costs, the price of day-old chickens, feed expenses, and harvest tonnage. Meanwhile, the inefficiency effect is substantially influenced by farmer age, education, household size, experience, and mortality ratio (MR). Reducing the MR can increase broiler yield, directly improving cost efficiency and, thus farmers’ income. Nonetheless, a comprehensive approach that includes training, monitoring, feedback, and incentivization is needed to enhance farmer performance in broiler contract farming.